2016
DOI: 10.1016/j.clinph.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prefrontal and parietal tDCS on learning and recognition of verbal and non-verbal material

Abstract: h i g h l i g h t stDCS over left or right PFC or PPC affects differentially encoding of verbal and non-verbal material. tDCS over PPC enhanced recognition of non-verbal items; tDCS over left PFC decreased recognition for both materials. Functional hemispheric lateralization does not follow the same rules throughout the brain. a b s t r a c tObjective: Information learned in a spaced way is usually better recognized than information learned in a massed way. The brain mechanisms underlying this spacing effect r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…As alertness measures did not significantly differ between the real and sham group, nor correlated with performance during either encoding or retrieval phase, we could minimize the possibility that the observed tDCS effects on the number of remembered words were a mere consequence of a favorable stimulation impact on low-level attention. Given the dual attentional hypothesis ( Cabeza, 2008 ), this may have been a confounding factor in studies that opted for the stimulation of the posterior parietal cortex (PPC) during the encoding phase of verbal learning paradigms ( Jones et al, 2014 ; Manuel and Schnider, 2016 ) as the PPC is primarily involved in attentional processes that subserve memory rather than mnemonic functions per se ( Berryhill, 2012 ). In spite of the absence of a relationship between attention and task performance in our study, the stimulation effects on other executive functions (e.g., working memory) that influence the performance in a verbal episodic memory task should be investigated in more detail in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As alertness measures did not significantly differ between the real and sham group, nor correlated with performance during either encoding or retrieval phase, we could minimize the possibility that the observed tDCS effects on the number of remembered words were a mere consequence of a favorable stimulation impact on low-level attention. Given the dual attentional hypothesis ( Cabeza, 2008 ), this may have been a confounding factor in studies that opted for the stimulation of the posterior parietal cortex (PPC) during the encoding phase of verbal learning paradigms ( Jones et al, 2014 ; Manuel and Schnider, 2016 ) as the PPC is primarily involved in attentional processes that subserve memory rather than mnemonic functions per se ( Berryhill, 2012 ). In spite of the absence of a relationship between attention and task performance in our study, the stimulation effects on other executive functions (e.g., working memory) that influence the performance in a verbal episodic memory task should be investigated in more detail in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Applied over the left DLPFC, anodal tDCS improved the rate of word list learning in healthy young participants ( Nikolin et al, 2015 ) as well as increased the performance of elderly individuals during the delayed recall of the learned items ( Sandrini et al, 2016 ). However, another study challenged the general enhancing effects of anodal tDCS, as its application resulted in a decreased recognition of verbal and non-verbal material ( Manuel and Schnider, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…different variables (affective valence [20,21], encoding instructions [22,23 Exp 3,24], number of items a studied item was presented in the study list [25,26], semantic relation across items in the study list [27], stimulus formats [28], type of recollection task [29,30], repeated encounter with the item before the test phase [31]).…”
Section: Data Extractionmentioning
confidence: 99%
“…Cathodal DLPFC tDCS has been shown to improve implicit learning outcomes for high-level motor tasks such as golf putting (Zhu et al, 2015) and cognitive flexibility (Chrysikou et al, 2013). Furthermore, it has been shown that tDCS has helped improve learning outcomes for implicit motor tasks, in which right parietal anodal stimulation resulted in greater neural efficiency through an improved task learning performance (Clark et al, 2012), as well as mental activities such as numerical competence (Cohen et al, 2010), network connectivity (Hunter et al, 2015) object detection during visual search (Bolognini et al, 2010; Clark et al, 2012; Tseng et al, 2012), spatial attention (Roy et al, 2015), and non-verbal material (Manuel and Schnider, 2016). Additionally, tDCS influence on parietal regions has shown a balance between the working memory capacity (skill) and the working memory task (Jones and Berryhill, 2012).…”
Section: Introductionmentioning
confidence: 99%